Experimental Analysis of the Influence of Process Parameters on Cylindricity in Turning Process - Cvetkovska, Marija; Stamenkova, Dragana; Lefkova, Anastasija; Vasileska, Ema; Tuteski, Ognen; Kusigerski, Boban; Vrtanoski, Gligorche (University Ss. Cyril and Methodius in Skopje, 2025)
Cylindrical parts produced through turning often demand certain form tolerances such as cylindricity to ensure proper function, reliability, and performance. As manufacturing shifts toward higher accuracy and sustainability, understanding how process parameters influence cylindricity becomes increasingly essential. This study presents an experimental analysis of the influence of three fundamental cutting parameters – depth of cut, feed rate, and spindle speed – on the cylindricity of parts produced under dry turning conditions. The experiments were performed on steel E335 using a full-factorial design with parameters varied at two levels. Cylindricity was measured on each machined part and statistically analyzed to evaluate individual effects and interactions of the parameters. Results show that all three parameters significantly affect cylindricity, with spindle speed exhibiting the highest statistical influence. Higher spindle speeds were associated with improved cylindricity, while increased feed rate and depth of cut tended to degrade form accuracy. A regression model was fitted to the experimental data to quantify the influence of each parameter and predict cylindricity actions based on cutting conditions. The findings align with recent literature and offer practical insights for optimizing dry turning operations to achieve higher geometric precision.
Keywords: turning process, design of experiment, regression analysis, cylindricity, process parameters